2021
DOI: 10.3390/en14020401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Braking Plates on the Aerodynamic Behaviors of a High-Speed Train Subjected to Crosswinds

Abstract: Using aerodynamic resistance to provide braking force for trains is an economical braking method. It has few components to wear out and requires no energy. But the aerodynamic braking plate will significantly affect train’s aerodynamics behaviors. This paper studies the effect of the braking plates’ layout on the aerodynamic force of head car when a train is running under a crosswind. The results show that the braking plate will not only increase the drag force, but also significantly affect the lift and later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In particular, the upstream braking plate will have an aerodynamic interference effect on the downstream braking plate when the train is equipped with multiple sets of braking plates [14]. Takami [15] combined the simulation and wind tunnel test and found that the drag of the braking plate was maximum at an opening angle of 75° to 85°, and there were a series of interference effects among the plates.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the upstream braking plate will have an aerodynamic interference effect on the downstream braking plate when the train is equipped with multiple sets of braking plates [14]. Takami [15] combined the simulation and wind tunnel test and found that the drag of the braking plate was maximum at an opening angle of 75° to 85°, and there were a series of interference effects among the plates.…”
Section: Introductionmentioning
confidence: 99%